Hegel, revolution, and the rule of law - Ramet, Sabrina P. (Eastern Review, 2020)
Georg Wilhelm Friedrich Hegel was one of the philosophic giants of the nineteenth century. Well versed in both ancient and more recent philosophical tracts, he rejected the individualism of Hobbes and Locke, as well as their notion that the state was an agency set up in the first place to protect life and property, and, drawing inspiration from Aristotle, outlined a vision of the state as an agency bound, in the first place, to protect the weak and the powerless. Hegel further rejected Kant’s individualistic ethics and counseled that ethical behavior had to be understood as taking place in a social context, with real duties toward other people. For Hegel, an individual had rights and duties within the context of the family, in the community, and, as a citizen, vis-à-vis the state. He emphasized the network of duties in which each individual finds himself, urging political moderation and concern for the good of the entire community. He has been condemned as a proto-totalitarian, lauded as a democrat of sorts, and described variously as liberal, anti-liberal, authoritarian, conservative-monarchist, and constitutionalist. This essay will argue that Hegel came to champion a constitutional-legal order (Rechtsstaat) under an autocratic monarch, with protection for liberal values. The absolute authority of the monarch, thus, was limited to those powers which he needed in order to advance and protect the interests of the citizens of the realm.